Domestic-level parliamentary scrutiny and voting behaviour in the European Parliament - Finke, Daniel (Government & opposition, 2014)
Inside the European Parliament political groups reveal levels of voting cohesion similar to that we observe in national parliaments. Faced with a conflict of interests between their national party and their European group, members of the European Parliament (MEPs) surprisingly often prioritize the latter principal over the former. In this article, I argue that domestic-level parliamentary scrutiny can have a tremendous impact on MEPs’ loyalties. Using data on the voting behaviour of German and Czech MEPs, I find that, under scrutiny, MEPs from governing parties are significantly more likely to vote against the instructions of their group leadership. The effect of domestic-level scrutiny on MEPs from opposition parties is weaker and depends on the dossier's political salience. These results provide further support for the strategic use of parliamentary scrutiny in European Union politics.
First published online 11 September 2013
Gesehen am 28.08.2020